EAST MEETS WEST: THE CURRENT STATE AND RESEARCH FINDINGS OF ADVANCE CARE PLANNING. (11th November 2018) - Inoue, M
Abstract: Advance care planning (ACP) is the process of planning for future medical care in the event that a person becomes unable to make decisions or speak for oneself. ACP has been promoted as a mechanism to respect a person's autonomy, which is one of the fundamental ethical principles in health care in both Japan and the United States. However, the condition of ACP in these two countries varies considering that cultural values and policies influence how ACP is implemented and practiced in society. This symposium will introduce the overview of ACP in Japan and the United States, including relevant policies, practices in place, current efforts, as well as challenges that these two countries face in relation to promoting ACP. The symposium will also present the most up-to-date research findings on ACP from these two countries, covering the prevalence rates of ACP, factors associated with the engagement in ACP, and people's perspectives on ACP. After comparing and contrasting differences, common goals and challenges are summarized and best practices will be discussed.